Mixed convection peristaltic motion of copper-water nanomaterial with velocity slip effects in a curved channel. (April 2017) - Hayat, T.; Farooq, S.; Alsaedi, A.
Highlights: Copper-water nanomaterial in peristalsis is modeled. First order velocity slip conditions are considered. Heat generation/absorption is presented. Heat transfer rate at upper wall of the channel is also discussed. Abstract: Background and objective : The primary objective of present analysis is to model the peristalsis of copper-water based nanoliquid in the presence of first order velocity and thermal slip conditions in a curved channel. Mixed convection, viscous dissipation and heat generation/absorption are also accounted. Method : Mathematical formulation is simplified under the assumption of small Reynolds number and large wavelength. Regular perturbation technique is employed to find the solution of the resulting equations in terms of series for small Brinkman number. The final expression for pressure gradient, pressure rise, stream function, velocity and temperature are obtained and discussed through graphs. Mathematica software is utilized to compute the solution of the system of equations and to plot the graphical results. Results : Results indicates that insertion of 30% copper nanoparticles in the basefluid (water) velocity and temperature reduces by almost 3% and 40% respecively. Moreover it is seen that size of the trapped bolus also reduces almost 20% with the insertion of 20% nanoparticles (copper) in the basefluid (water). Conclusion : It is noted that velocity and temperature are decreasing functions of nanoparticle volume fraction. Moreover the temperature rises when heat generation parameter and Brinkman number are enhanced.